Islamic Urdu Literature: A Heretical Islamic Literature in Indian Subcontinent - Shamsuddin, Salahuddin (Advances in Social Sciences Research Journal, 2023)
The Intellectual heritage of India is an integral part of Islamic civilization in Indian subcontinent and the development of Islamic civilization in India represents a regional pattern or a local formation of this civilization that occurred as a reaction and in response to the developments that were the result of Islam’s insistence on survival in India and its fear for itself of being lost. The link among Urdu, Persian, Arabic and Turkish literatures is that each of them is considered influenced in its dimensions by Islamic civilization that emerges from the religion, science and art, and it is not permissible under any circumstances to sever the link among them, and we give an example for that saying that Persian literature is influenced by Arabic literature and the ancient Turkish literature is influenced by Persian literature influenced by Arabic literature, and Urdu literature is influenced by Arabic, Persian and Turkish literature, and from here we find similarities among these literatures that depict and speak about Islamic civilization in its various manifestations. Language of these different literatures is influenced by Arabic, as they contain countless Arabic words that evidence that they are all branched out from one origin, which is Islamic religion.